A Synopsis of the American Journal of Evaluation: Volume 26(3) - Bianca Montrosse (Journal of MultiDisciplinary Evaluation, 2006)
The current issue of the American Journal of Evaluation (AJE) is one of the more comprehensive issues, in that articles for seven of the ten AJE sections are included. What follows is a summary of the articles in the order in which they appear.